PENGARUH PEMBERIAN EKSTRAK AKAR TUBA (Derris elliptica) TERHADAP LAMA WAKTU PEMBIUSAN BENIH IKAN MAS (Cyprinus carpio) - Tobigo, Desiana Trisnawati; Madinawati, Madinawati; Mariana, Mariana (FAPETKAN UNTAD, 2017)
This study aimed to determine the effect of extract tuba root (Derris elliptica) the length of time anesthesia carp (Cyprinus carpio). This study was conducted in March 2016, using the research material 180 carp fry and given a dosage of different tuba root extract, namely A (0.8 ml / 5 L of water), treatment B (1 ml / 5 L of water) , treatment C (1.2 ml / 5 L of water). Parameters measured were anesthetized seeds start time and duration anesthetized goldfish carp seed. Analysis of data using analysis completely randomized design (CRD) with a further test Significant Difference (LSD). The results showed that higher doses of tuba root extract the faster start time sedated and the longer duration of anesthesia seed carp. Treatment C (1.2 ml / 5 L of water) to give effect anesthetized fastest start time (28.25 minutes) and gave effect anesthetized longest time (205 minutes), whereas treatment A (0.8 ml / 5 L of water) to give influence anesthetized longest start time (41.10 minutes) and gave effect anesthetized fastest (111.17 min). The higher the dose of tuba root extract the faster start time sedated and the longer duration of anesthesia seed carp.Keyword: anesthesia, extract, tuba root, hatchery